Monetary Growth and Exchange Rate Depreciation As Causes of Inflation in African Countries : An Empirical Analysis - Canetti, Elie (IMF Working Papers; Working Paper ;, 1991)
This paper examines the relative importance of monetary growth and exchange rate depreciation as causes of inflation in a sample of 10 Sub-Saharan African countries. Causality tests and impulse response functions derived from vector autoregression (VAR) analysis suggest that both monetary expansion and exchange rate adjustments cause inflation in a number of these countries. However, the failure of the tests to attribute the bulk of the variance in inflation in most of the countries to either variable suggests either a problem with the statistical technique or that some other factor--perhaps structural bottlenecks or a measure of overall macroeconomic policy stance incorporating both monetary and exchange rate policy--may be even more important as a determinant of inflation in African countries.